The influence of bearing grease composition on friction in rolling/sliding concentrated contacts. (February 2016) - De Laurentis, Nicola; Kadiric, Amir; Lugt, Piet; Cann, Philippa
Abstract: This paper presents new results examining the relationship between bearing grease composition and rolling-sliding friction in lubricated contacts. Friction coefficient and lubricating film thickness of a series of commercially available bearing greases and their bled oils were measured in laboratory tribometers. Test greases were selected to cover a wide spectrum of thickener and base oil types, and base oil viscosities. The trends in measured friction coefficients were analysed in relation to grease composition in an attempt to establish the relative influence of individual grease components on friction. Two distinct operating regions with markedly different friction behaviour are identified for each grease. At relatively high speeds the greases behave approximately as their bled/base oils, while in the low speed region the frictional response is very dependent on their thickener type and properties of the lubricating film. Low viscosity, synthetic base oil seems to offer efficiency advantages in the high speed region regardless of thickener used, while the choice of thickener type is significant under low speed conditions. Highlights: Relationship between bearing grease composition and friction is examined. Friction and film thickness of a range of greases and their bled oils are measured. At low speeds the frictional response is very dependent on grease thickener type. At high speeds low viscosity, synthetic base oils offer efficiency advantages.